Isolation and Biological Activity of Naturally Occurring Compounds from Melicope Lunu Ankenda (Gaertn) T-Hartley, Melicope Bonwickii(F-Muell) Tharyley and Tetradium Sambucinum (Bl) Hartley - Komala, Ismiarni (2005)
Detailed investigation on three Rutaceous plants have resulted in the isolation and structural elucidation of a number of compounds. The structures of these compounds were elucidated by using spectroscopic methods such as W (ultraviolet), IR (infia red), MS (mass spectra), NMR (Nuclear Magnetic Resonance) and also by comparison with previous reports. The crude extracts and isolated compounds were evaluated for their antioxidant, cytotoxicity and antimicrobial activities using DPPH (1,l -diphenil-2-picrylhydrazyl), MTT ((3-(4,5-dimethylthiazol-2-y1)-2,sdiphenyltetrazolium bromide) and disc diffusion methods, respechvely. The phytochemical study on leaves of Mel~cope lum-ankenda (Gaertn) T. Hartley afforded pO-geranylcoumaric acid (1 53) sesamin (1 Og), melisemine (1 54) and a new compound given tentative structure of 7,7"-digeranyloxy-2",3"-epoxycinnamic anhydride (155). The melisemine (154) showed weak activity as a radical scavenger with an ICso value of 75 pg/mL. Meanwhile the 7,7"-digeranyloxy-2",3"- epoxycinnamic anhydride (155) was found to be active against cervical cancer (Hela) cell line with an ICSOv alue of 34 pg/mL. The investigations on leaves of hfelicope bonwickii (F. Ibluell) T. Hartley have resulted in the isolation of three known furoquinoline alkaloid, 7-(2',3'- epoxypreny1oxy)-4-methoxyfuroquinoline (156), evellerine (157) and kokusaginine (11) together with a new 7-(2'-hydroxy-3'-ch1oroprenyloxy)-4- methoxyfuroquinoline (158) and a known amide compound aurantiamide acetate (1 59). Two compounds 7-(2',3 '-epoxypreny1oxy)-4-methoxyfuroquinoline (1 56) and 7-(2'-hydroxy-3'-cl~1loroprenyloxy)-4-methoxyfuroquinol~(e1 58) were found to be toxic to cervical cancer (Hela) cell line with ICso values of 6.0 and 11.4 pg/mL, respectively. Detailed extraction and separation of bark and leaves of Tetradium sambucinum (BI) Hartley have led to the isolation of decarine (160), rutaecarpine (122) 7- hydroxycoumarin (141) and aurantiamide acetate (159). Decarine (160) was active against the cervical cancer cell lines (Hela) with an ICW value of 14.6 pg/mL, while rutaecarpine (122) showed weak a radical scavenger activity with an ICjo value of 75pg/mL.